Prevalence of Leishmania infantum Infection in Dogs Living in an Area of Canine Leishmaniasis Endemicity Using PCR on Several Tissues and Serology - Solano-Gallego, Laia (American Society for Microbiology, 2001)
We studied and compared the prevalence of Leishmania infection and the seroprevalence and the prevalence of canine leishmaniasis in an area where canine leishmaniasis is endemic. One hundred dogs living on the island of Mallorca (Spain) were studied. In this study, we clinically examined each dog for the presence of symptoms compatible with leishmaniasis, determined the titer of anti-Leishmania antibodies, and investigated the presence of Leishmania DNA by PCR in skin, conjunctiva, and bone marrow samples of each dog. The prevalence of the disease and the seroprevalence were 13 and 26%, respectively. In 63% of the dogs, Leishmania DNA could be detected by PCR in at least one of the tissues studied. The results of positive PCR in the bone marrow, the conjunctiva, and the skin were 17.8, 32, and 51%, respectively. The prevalence of the infection, 67%, was calculated using all animals that were seropositive and/or positive by PCR with any tissue. The results showed that the majority of dogs living in an area where canine leishmaniasis is endemic are infected by Leishmania and that the prevalence of infection is much greater than the prevalence of overt Leishmania-related disease.